2021
DOI: 10.1177/0961203321992117
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Annexin A2 and cerebral thrombosis: Insights from a mouse model

Abstract: Introduction Antiphospholipid syndrome (APS) is an autoimmune disorder manifested by thromboembolic events, recurrent spontaneous abortions and elevated titers of circulating antiphospholipid antibodies. In addition, the presence of antiphospholipid antibodies seems to confer a fivefold higher risk for stroke or transient ischemic attack. Although the major antigen of APS is β2 glycoprotein I, it is now well established that antiphospholipid antibodies are heterogeneous and bind to various targets. Recently, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although relatively small, the presence of a motor impairment complicates drawing concrete conclusions from the behavioral tests, which measure anxiety and spatial memory based on locomotion. Previous studies supporting anxiety modifications in animal models of antiphospholipid syndrome suggest an interaction between inflammation, coagulation, and anxiety [ 46 , 47 , 48 ]. Future studies may need to focus on cognitive evaluation assessed at different points in time or should include observational studies on the effect of infection on NfL in human subjects in relevant clinical scenarios in which enoxaparin is indicated as part of routine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although relatively small, the presence of a motor impairment complicates drawing concrete conclusions from the behavioral tests, which measure anxiety and spatial memory based on locomotion. Previous studies supporting anxiety modifications in animal models of antiphospholipid syndrome suggest an interaction between inflammation, coagulation, and anxiety [ 46 , 47 , 48 ]. Future studies may need to focus on cognitive evaluation assessed at different points in time or should include observational studies on the effect of infection on NfL in human subjects in relevant clinical scenarios in which enoxaparin is indicated as part of routine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…101 A study in 2021 revealed that the level of anti-ANXA2 antibodies in APLS patients was significantly higher than that in normal control subjects, and the thrombosis rate was significantly increased in mouse models with elevated anti-ANXA2 antibodies. 102 Therefore, the detection of anti-ANXA2 antibodies in serum of APLS patients might be a useful guide for prophylactic treatment of thrombosis. 101,102 Upregulation of ANXA2 on the cell membrane accelerates plasmin production, and excessive plasmin causes surrounding tissue damage and even bleeding.…”
Section: The Role Of Anxa2 Heterotetramer In Thrombosis and Coagulopathymentioning
confidence: 99%
“…102 Therefore, the detection of anti-ANXA2 antibodies in serum of APLS patients might be a useful guide for prophylactic treatment of thrombosis. 101,102 Upregulation of ANXA2 on the cell membrane accelerates plasmin production, and excessive plasmin causes surrounding tissue damage and even bleeding. 103 APL is one of the most representative cases.…”
Section: The Role Of Anxa2 Heterotetramer In Thrombosis and Coagulopathymentioning
confidence: 99%
See 1 more Smart Citation
“…139 140 Anti-ANXA2 antibodies are related to worse outcomes in ischemic stroke mice. 141 This may be related to the reduced fibrinolytic capacity described above, or to other direct effects on neurons or glia.…”
Section: Coagulation Involvement In Cns Immunologymentioning
confidence: 99%